Evaluasi Media Pembelajaran Berbasis Aplikasi Capcut Dengan Tema Praktek Sholat Jenazah - suprapto, Muhammad; Febrianto, Rian (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
Learning media is an important component that is useful for increasing students' understanding and involvement in the teaching and learning process. For this reason, researchers want to develop one of the media that is quite popular for learning, namely in the form of a Capcut module with the theme of the practice of funeral prayers for Madrasah Aliyah Miftahul Jannah Selatbaru. This research aims to develop learning media in the form of a Capcut module with the theme of the practice of funeral prayers for Madrasah Aliyah Miftahul. Jannah Selatbaru. Using Research and Development (R&D) methodology, this research went through systematic steps, including analysis, design, validation, implementation and evaluation. This approach also collects empirical data to ensure the resulting product is relevant and practical. This research involved 24 teachers and 39 students as respondents through a questionnaire. The results of the research can be seen regarding the use of Capcut media in learning. Research results shows that the value of the learning media components assessed by 24 teachers obtained an average of 4.55 with a standard deviation of 0.14 in the Strongly Agree category, and 39 students obtained an average of 5.08 and a standard deviation of 0.32 with category strongly agree. The results of the questionnaire assessment for teachers and students showed that the numerical scale strongly agreed on the third dimension in the questionnaire. In conclusion, Capcut media can be said to be a good medium for the learning process, especially regarding the practical material for funeral prayers. This research recommends integrating modern technological learning media into the teaching of Fiqh lessons to support interactive and effective learning activities in today's modern times.